2019
DOI: 10.1017/s1041610219000826
|View full text |Cite
|
Sign up to set email alerts
|

Decision aids to support decision-making in dementia care: a systematic review

Abstract: Objectives:We aimed to critically evaluate decision aids developed for practitioners and caregivers when providing care for someone with dementia or for use by people with dementia themselves. Decision aids may be videos, booklets, or web-based tools that explicitly state the decision, provide information about the decision, and summarize options along with associated benefits and harms. This helps guide the decision maker through clarifying the values they place on the benefits or harms of the options.Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 34 publications
1
67
0
Order By: Relevance
“…Carers may benefit from support with making decisions (Mathew et al, 2016) to better understand their options and the benefits of when a palliative approach may be appropriate. Decision aids which provide information on the decision and the options available have shown promise to support family carers (Davies et al, 2019a), this may include novel approaches such as simple rules of thumb. Rules of thumb have been successfully used with professionals when making decisions about end-of-life care for people with dementia (Davies et al, 2018).…”
Section: End-of-life Decision-makingmentioning
confidence: 99%
“…Carers may benefit from support with making decisions (Mathew et al, 2016) to better understand their options and the benefits of when a palliative approach may be appropriate. Decision aids which provide information on the decision and the options available have shown promise to support family carers (Davies et al, 2019a), this may include novel approaches such as simple rules of thumb. Rules of thumb have been successfully used with professionals when making decisions about end-of-life care for people with dementia (Davies et al, 2018).…”
Section: End-of-life Decision-makingmentioning
confidence: 99%
“…Implications for future research, policy, and clinical practice This review has identified the necessary steps in making decisions regarding nutrition and hydration for PLWD; it can guide healthcare practitioners and policy makers on what issues they should be aware of, how and when to address the issues in the decision-making process and whom they should involve in the decisions. In the later stages, family caregivers and practitioners can be facilitated with decisional support, for example, a decision aid which has been found to increase the level of knowledge, improve quality of communication and reduce decisional conflicts [75]. This review helps to guide the focus of decisional support and identify mechanisms to overcome many of the identified barriers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In another study, Sinclair et al, show how it is possible to support the person in making decisions by employing “Augmentative and Alternative Communication” (AAC) techniques combining multiple sensory modalities (e.g., aural and visual), observing facial expressions, body language, sounds made by the person, or eye contact, and using structured approaches to communication ( 106 ). Support can also come from IT decisional aids sending reminders to the person or guiding them through the decisional process ( 111 , 112 ). Finally, just creating a quieter and tidier environment and encouraging the person to express their wishes ( 21 , 62 , 109 ), or defending them from others' disempowering behavior ( 105 ) may be important means of support.…”
Section: The Crpd Dementia and Healthcare Decisionsmentioning
confidence: 99%